Molecular epidemiology of hepatitis C virus (HCV) in Greece: temporal trends in HCV genotype-specific incidence and molecular characterization of genotype 4 isolates. - Katsoulidou, A; Sypsa, V; Tassopoulos, N; Boletis, J; Karafoulidou, A; Ketikoglou, I; Tsantoulas, D; Vafiadi, I; Hatzis, G; Skoutelis, A; Akriviadis, E; Vasiliadis, T; et al. (2006)
This study aimed to estimate the overall HCV genotype distribution and to reconstruct the HCV genotype-specific incidence in Greece during the recent decades. It also focused at the identification of genotype 4 subtype variability in Greek isolates. A total of 1686 chronically infected HCV patients with detectable serum HCV RNA by RT-PCR, belonging to different risk groups were studied. Amplified products from the 5'-noncoding region were typed using a commercially available assay based on the reverse hybridization principle. The HCV genotype-specific incidence was estimated using a previously described back calculation method. HCV genotype 1 was the most prevalent (46.9%) followed by genotype 3 (28.1%), 4 (13.2%), 2 (6.9%) and 5 (0.4%). A high prevalence of genotype 1 (66.3%) in haemophilia patients was recorded whereas HCV genotype 3 was found mainly among patients infected by I.V. drug use (58.2%). Data on the temporal patterns of HCV genotype-specific incidence in Greece revealed a moderate increase (1.3-1.6 times) for genotypes 1 and 4, and a decrease (1.5 times) for genotype 2 from 1970 to 1990, whereas there was a sharp (13-fold) increase for genotype 3. The molecular characterization of 41 genotype 4 HCV isolates belonging to various risk groups revealed that, subtype 4a was the most frequently detected (78%). Phylogenetic comparison of the Greek 4a isolates with all HCV-4a isolates reported worldwide so far revealed a topology which does not discriminate Greek isolates from the others. HCV-4 does not represent a recent introduction in Greece.